Controlling the release of hydrophobic compounds by a supramolecular amphiphilic assembly. Issue 45 (18th April 2016) - Kashapov, Ruslan R.; Rassadkina, Regina I.; Ziganshina, Albina Yu.; Mukhitova, Rezeda K.; Mamedov, Vakhid A.; Zhukova, Nataliya A.; Kadirov, Marsil K.; Nizameev, Irek R.; Zakharova, Lucia Ya.; Sinyashin, Oleg G.
Abstract : Here, we report a novel approach of using a supramolecular system based on calix[4]resorcinarene and surfactant to facilitate the release of hydrophobic compounds. Abstract : Here, we report a novel approach of using a supramolecular system based on calix[4]resorcinarene and surfactant to facilitate the release of hydrophobic compounds. This finding is an important step towards the development of controlled-release formulations for water-insoluble drugs.